Poverty and Inequality (London : C. W. Publishing Ltd.)
1944-10 1944 1940s 29 pages 10 G.D.H. Cole compares the diet of an ordinary working-class family of five persons with an income of £3 a week with that of a middle-class family of the same size with about £500 or £600 a year. It should be noted that the contrast here is not between the richest and the poorest, but between typical working-class and middle-class families. In the following table the approximate consumption of certain foods by the middle class family is expressed as a percentage of the consumption of the same foods by the working Bread and Flour ............................................. 88 per cent. Potatoes ....................................................... 84 per cent. Meat .............................................................. 136 per cent. Fish ............................................................. 200 per cent. Eggs ............................................................ 168 per cent. Butter .......................................................... 136 per cent. Cheese.......................................................... 138 per cent. Milk (condensed included)................................. 200 per cent. Sugar, Jam, etc............................................... 120 per cent. Tea ............................................................. 100 per cent Fruit ............................................................ 230 per cent. Vegetables (other than potatoes) ........................ 300 per cent. (3) The extent of Matnutrition. Sir John Orr, as a result of a survey made in 1934, came to the startling conclusion that one-third of the nation was then suffering from malnutrition. He divided the population into groups as follows :— Weekly Income per head. Average Weekly Expenditure on Food per head. Estimated Population of the Group. Nos. in thousands. Percentage of Total. Group 1 Up to 10/- 4/- 4,500 10 Group 2 10/- to 15/- 6/- 9,000 20 Group 3 15/- to 20/- 8/- 9,000 20 Group 4 20/- to 30/- 10/- 9,000 20 Group 5 30/- to 45/- 12/- 9,000 20 Group 6 Over 45/- 14/- 4,500 10 Group 1 would contain, for example, all those families of more than three persons who were living on unemployment benefit. The diet of these people — 1/10 of the nation — was grossly deficient in every essential constituent. Group 2, in which would fall the ordinary working-class family with an income of £3 a week between five persons, had a diet less seriously deficient, but nevertheless lacking in vitamins and minerals. Both these groups had a diet deficient in total calories — that is, neither was even getting enough to eat. Group 3 would contain the skilled workman, the most prosperous member of his class. Yet he too was unable to afford a fully balanced diet. * Condition of Britain G.D.H. Cole, page 128. † Food, Health and Income, Sir John Orr, page 27. 15X/2/98/13